Pengembangan Aplikasi Single Investor Identification (SID) Pasar Modal Indonesia Berbasis Web Menggunakan Metode Extreme Programming - Fawwaz, Sya'diyah Nur; Munir, Sirojul; Wiyono, Bambang Harie (LPPM STT Terpadu Nurul Fikri, 2025)
Kustodian Sentral Efek Indonesia (KSEI) is an authorized capital market institution. One of its programs is providing a Single Investor Identification (SID) for the diaspora or Indonesian people living abroad; this SID will act as a single investor identity in the Indonesian Capital Market. This study investigates the design of a Web-Based Diaspora Investment Information System using the .NET Framework, with a primary focus on the business process of obtaining a SID for diaspora investors. The system was developed through iterative planning, design, coding, and testing phases using the Agile Extreme Programming software engineering method. This strategy was chosen since it enabled significant stakeholder participation and flexibility in response to changes throughout the development process. The results of the Blackbox Testing test evaluation method on the application's functionality showed that all 85.7% of the application's features worked well, and the results of feedback on the use of the application by users obtained a score of 88.33%; these results indicate that this application can be used and help PT Custodian Sentral Efek Indonesia to record prospective diaspora investors in the Indonesian Capital Market.